(untitled) (Perspectivas em Ciência da Informação, 2007)
The article deals with the potential role of electronic information networks and inter-firm networks as a determining factor for greater integration and cooperation among the newly-industrialized countries in the light of research carried out by other authors, who point to these networks as mechanisms that merely reinforce already-existing global inequalities.